2019
DOI: 10.1021/acs.oprd.9b00021
|View full text |Cite
|
Sign up to set email alerts
|

Development, Optimization, and Scope of the Radiosynthesis of 3/5-[18F]Fluoropyridines from Readily Prepared Aryl(pyridinyl) Iodonium Salts: The Importance of TEMPO and K2CO3

Abstract: A robust process for the radiosynthesis of 3/5-[ 18 F]fluoropyridines has been developed by radiofluorination of iodonium triflates using K 18 F/K 2 CO 3 /K 222 complex in the presence of TEMPO. Both electronically deficient and enriched iodonium salts were readily obtained from the corresponding 3/5-iodopyridines and afforded the corresponding 3/5-[ 18 F]fluoropyridines in 6−78% yields. The concentrations of K 2 CO 3 and TEMPO were found to be crucial for the radiofluorination efficiency. The process was vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Diaryliodonium salts appear as fairly appealing electrophilic arylating reagents as well as precursors for positron emission tomography (PET) [39,40]. They are powerful intermediates for the synthesis of a broad range of radiofluorinated synthons and clinically relevant PET tracers [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]. Since the pioneering works on the palladium-and copper-catalyzed arylation of sp2 C-H indoles reported respectively by Sanford [57] and Gaunt groups [58], Nand C-arylation involving diaryliodonium salts offer a highly complementary strategy for the synthesis and derivatization of heteroarenes (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Diaryliodonium salts appear as fairly appealing electrophilic arylating reagents as well as precursors for positron emission tomography (PET) [39,40]. They are powerful intermediates for the synthesis of a broad range of radiofluorinated synthons and clinically relevant PET tracers [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]. Since the pioneering works on the palladium-and copper-catalyzed arylation of sp2 C-H indoles reported respectively by Sanford [57] and Gaunt groups [58], Nand C-arylation involving diaryliodonium salts offer a highly complementary strategy for the synthesis and derivatization of heteroarenes (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…The F-substituted 2,4-PDCA derivatives may also be of use as 19 F NMR probes in fluorine chemical shift anisotropy and exchange high-throughput screening for protein binding [ 46 , 47 ]. Recent advances in fluorination reactions suitable for the rapid late-stage introduction of radioactive 18 F atoms into hetereoaromatic scaffolds [ 48 , 49 ], including in substituted pyridines such as fluorinated derivatives of the multiple sclerosis drug 4-aminopyridine [50] , [51] , [52] , suggest the F-substituted 2,4-PDCA derivatives might be useful scaffolds for positron emission tomography (PET) studies.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that coupling of aryl halides (bromide and iodide) with biaryl thiophenols tolerates a broad range of functional groups [ 19 ]. The subsequent oxidation-cyclisation reaction sequence is highly robust and enables facile synthesis of labelling precursors of complex ligands that otherwise are difficult to access, such as UCB-J [ 48 , 49 ] (We were unable to prepare the precursor using the method reported in reference [ 19 ]), electron-deficient substrates as exemplified by FNDP, and 3-pyridines which are challenging to label with alternative strategies [ 53 ]. While further studies are needed to determine the scope of the oxidation and cyclisation steps, it is worth noting that periodic acid typically requires a catalyst to mediate oxidation of other functional groups, with the exception of anilines, unprotected amino acids, and 1,2-diols [ 54 ].…”
Section: Discussionmentioning
confidence: 99%